Prática refllexiva e trabalho pedagógico entre contornos e sombras de um livro didático de arte - BRISOLLA, Livia Santos (2009)
The recearch reflexive practive and pedagogic work: shadow and shapes of a didatic work book, develops an analisys of a pedagogic experience inspired on a didatic work book. ART AND HABILITIES , book II. The didactic book is seen, primary as a cultural workmanship that joins knowledge and works studies, in order to orient teachers pedagogic work. It is now considered to be a source of original ideas to the recearcher teacher and lately also as an experimental field of studies to the students as a reference. That investigation is built from the observation and relationship between children of 8 and 9 as to live reflexive and creatives practices. I point out here the capacity of observing and interpreteting images as essencial to educate people to have a reflexive and creative position in an intelligent and critical way with textual and visual images as the book shows. As a teacher and also as a recearcher I feel like to reflect and to work my teacher practice from the relationship and conceptions with my students to set new ways to develop the work in the classroom, sharing different pedagogic practices. That investigation shows the urgency of analizing the objective of the didactic book connected with living experiences of the students and particulary to the teacher as an important hole to interfere in that process.